Long-term Impacts of Household Electrification in Rural India - van de Walle, Dominique; Ravallion, Martin; Mendiratta, Vibhuti; Koolwal, Gayatri (World Bank, Washington, DC, 2013)
India's huge expansion in rural electrification in the 1980s and 1990s offers lessons for other countries today. The paper examines the long-term effects of household electrification on consumption, labor supply, and schooling in rural India over 1982-99. It finds that household electrification brought significant gains to consumption and earnings, the latter through changes in market labor supply. It finds positive effects on schooling for girls but not for boys. External effects are also evident, whereby households without electricity benefit from village electrification. Wage rates were unaffected. Methodologically, the results suggest sizeable upward biases in past estimates of the gains from electrification associated with how past analyses dealt with geographic effects.